Penggunaan Media Youtube Dalam Materi Colors Untuk Meningkatkan Kosakata Bahasa Inggris Siswa Kelas I SD Negeri 3 Rendang - Sukada, I Putu; Kusuma, I Komang Nada; Numertayasa, I Wayan (Dharmas Education Journal (DE_Journal), 2025)
This study aims to improve the English vocabulary mastery of first-grade students at Rendang Public Elementary School 3 on the topic of Colors through the implementation of YouTube as a learning medium. The research employed a Classroom Action Research (CAR) method conducted in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. The subjects of this study were 17 first-grade students in the odd semester of the 2025/2026 academic year. Data were collected through tests, observations, and field notes, then analyzed using descriptive quantitative and qualitative approaches. The results showed a significant increase in students’ average vocabulary scores—from 51.96 in the pre-test to 87.78 in the post-test of the first cycle, and from 67.59 to 89.68 in the second cycle. In addition to academic improvement, students also showed more active, enthusiastic, and participatory learning behavior during the teaching process. The use of YouTube videos combining visual, auditory, and kinesthetic elements proved effective in strengthening students’ vocabulary retention while creating a fun and interactive learning environment. Therefore, YouTube is considered an effective and contextual medium for teaching English vocabulary, aligning with the principles of the Merdeka Curriculum, which emphasizes creativity, active participation, and learner autonomy.